Prognostic value of the interval from surgery to initiation of radiation therapy in correlation with some histo-clinical parameters in patients with malignant supratentorial gliomas - Gliński, Bogdan; Urbański, Jacek; Hetnał, Marcin; Małecki, Krzysztof; Jarosz, Magdalena; Mucha-Małecka, Anna; Chrostowska, Agnieszka; Jakubowicz, Ewa; Frączek-Błachut, Beata; Dymek, Paweł (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : To determine the relationship between the interval from surgery to initiation of radiation therapy (ISRT) and prognostic factors, such as age, performance status, tumour location, extent of surgical resection and tumour histology in patients with malignant gliomas. Materials and methods : From 1995 to 2005, 308 adults patients with supratentorial malignant gliomas (198 glioblastomas, and 110 anaplastic astrocytomas) received postoperative radiotherapy with radical intent. A total tumour dose of 60 Gy in 30 fractions in 6 weeks was delivered. ISRT varied from 15 to 124 days, with median time of 37 days, and it was a cut-off value to assess the results. The end point in our study was two-year overall survival. Results : The two-year overall survival rate in the whole group was 17%, with 24% for patients with ISRT value  37 days, and 14% for patients with an interval longer than 37 days (p = 0.042). Univariate analysis showed that delayed initiation of radiotherapy influenced the outcome of patients with glioblastoma older than 40 years, and with other than frontal location of tumour. Two-year overall survival rates for ISRT  37 days were 15%, 18% and 22% respectively, compared to 8%, 4% and 11% for ISRT > 37 days. In a multivariate analysis (Cox’s model) the only variables that were significantly associated with worse survival were older age and ISRT prolonged for more than 37 days. Conclusion : The study showed longer than 37 days waiting time from surgery to initiation of radiotherapy to be a significant predictor of overall survival for adult patients with malignant supratentorial gliomas.